KETAMINE INHIBITS ULTRASOUND STIMULATION-INDUCED NEUROMODULATION BY BLOCKING CORTICAL NEURON ACTIVITY - Han, Sungmin; Kim, Minkyung; Kim, Hyungmin; Shin, Hyunjoon; Youn, Inchan (ELSEVIER SCIENCE INC, 2018)
Ultrasound (US) can be used to noninvasively stimulate brain activity. However, reproducible motor responses evoked by US are only elicited when the animal is in a light state of anesthesia. The present study investigated the effects of ketamine on US-induced motor responses and cortical neuronal activity. US was applied to the motor cortex of mice, and motor responses were evaluated based on robustness scores. Cortical neuronal activity was observed by fluorescence calcium imaging. US-induced motor responses were inhibited more than 20 min after ketamine injection, and US-triggered Ca2+ transients in cortical neurons were effectively blocked by ketamine. Our results indicate that ketamine suppresses US-triggered Ca2+ transients in cortical neurons and, therefore, inhibits US-induced motor responses in a deep anesthetic state. (C) 2018 World Federation for Ultrasound in Medicine & Biology. All rights reserved.
Keywords: NONINVASIVE BRAIN-STIMULATION; FOCUSED ULTRASOUND; TRANSCRANIAL ULTRASOUND; HIPPOCAMPAL-NEURONS; INHALED ANESTHETICS; CA2+ OSCILLATIONS; IN-VITRO; PARAMETERS; CURRENTS; CORTEX